From Conventional to Innovative Approaches for Pain Treatment 2019
DOI: 10.5772/intechopen.84580
|View full text |Cite
|
Sign up to set email alerts
|

Features and Clinical Effectiveness of the Regenerative Injection Treatments: Prolotherapy and Platelet-Rich Plasma for Musculoskeletal Pain Management

Abstract: Pain is a symptom caused by a disease process and/or tissue injury. With the prolongation of life expectancy in humans, the incidence of degenerative joint diseases and as a result pain has increased. Unfortunately, a method of treatment that stops or reverses progression by affecting the pathogenesis in these diseases has not been developed. Physical therapeutics such as medicine and physical rehabilitation often are prescribed for patients suffering with pain. Recently, in addition to these routine therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Various injection types and methods are available in the literature for different hip pathologies [7,8]. Prolotherapy (PrT) is an injection method successfully used in the degenerated and damaged joint structures including tendons, cartilage, and other connective tissues [9][10][11][12][13][14][15]. Previous studies have shown that dextrose has a neurogenic effect on pain at 5% concentrations [16,17], creates non-inflammatory ligament growth at 10% concentration [18] and, at more than 10% concentration, initiates a brief inflammatory cascade which promotes fibroblast growth and subsequent collagen production [19], and appears to be chondrogenic [20], thereby providing healing and tissue renewal.…”
Section: Introductionmentioning
confidence: 99%
“…Various injection types and methods are available in the literature for different hip pathologies [7,8]. Prolotherapy (PrT) is an injection method successfully used in the degenerated and damaged joint structures including tendons, cartilage, and other connective tissues [9][10][11][12][13][14][15]. Previous studies have shown that dextrose has a neurogenic effect on pain at 5% concentrations [16,17], creates non-inflammatory ligament growth at 10% concentration [18] and, at more than 10% concentration, initiates a brief inflammatory cascade which promotes fibroblast growth and subsequent collagen production [19], and appears to be chondrogenic [20], thereby providing healing and tissue renewal.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of SS formation is the damage of the tibia where the adhesion site of the posterior lower leg muscles as a result of overuse. In the treatment of prolotherapy, injection is applied to the enthesis where the muscle adheres to the bone 9 . Although the diagnosis of enthesopathy is unclear, prolotherapy has focused on enthesis as a source of chronic low back pain 22 .…”
Section: Discussionmentioning
confidence: 99%
“…But, there is no published randomized controlled trial with these various injection techniques for SS in the literature 5 . Prolotherapy has proven to be a safe and effective procedure because of its healing or regeneration ability for soft tissues when used in chronic musculoskeletal conditions such as low back pain, tendinopathy, osteoarthritis 8,9 . After an injury if an inadequate repair occurs, pain and disability can emerge from degenerated ligaments, tendons, cartilage, and enthesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations